Peran Artificial Intelligence dalam meningkatkan kualitas Pendidikan Agama Islam - Rois, Muhammad Aminuddin; Saputra, Rohmad Nurul Aji; Saefudin, Ahmad (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2025)
Technology has a significant impact on the formation of morals, ethics, morals and individual norms, especially for children who are in the education process. Since the advent of technology, there appears to be a decline in morals among children, where many of them prefer to play games or use social media, such as TikTok, and focus on activities such as top ups, rather than undergoing education, both formal and non-formal. . Apart from that, the influence of the social environment makes them tend to ignore their parents. This research adopts a qualitative approach and aims to explore the role of Artificial Intelligence (AI) technology in improving the quality of Islamic religious education (PAI). With rapid progress in the field of AI, there is great potential that can be exploited to improve learning methods and increase access to information in the PAI context. This research examines how AI technology can contribute to improving the quality of PAI. Rapid technological developments provide opportunities for AI to revolutionize learning methods and interactions between educators and students. AI, as a field of science that focuses on developing computers and systems capable of carrying out tasks that require human intelligence, has the potential to provide significant benefits in education. In the context of basic education, the presence of AI can optimize the learning process. By utilizing AI technology, teachers can monitor individual student learning progress and identify weaknesses or special needs that need to be addressed. The AI system can also provide learning recommendations tailored to student needs, thereby increasing the effectiveness of the educational process. Abstrak Teknologi memiliki dampak yang signifikan terhadap pembentukan akhlak, etika, moral, dan norma individu, terutama bagi anak-anak yang sedang dalam proses pendidikan. Sejak hadirnya teknologi, tampak adanya penurunan moral di kalangan anak-anak, di mana banyak dari mereka lebih memilih untuk bermain game atau menggunakan media sosial, seperti TikTok, serta berfokus pada aktivitas seperti top up, ketimbang menjalani pendidikan, baik formal maupun non-formal. Selain itu, pengaruh lingkungan sosial membuat mereka cenderung mengabaikan orang tua. Penelitian ini mengadopsi pendekatan kualitatif dan bertujuan untuk mengeksplorasi peran teknologi Kecerdasan Buatan (AI) dalam meningkatkan kualitas pendidikan agama Islam (PAI). Dengan kemajuan yang pesat dalam bidang AI, terdapat potensi besar yang dapat dimanfaatkan untuk memperbaiki metode pembelajaran serta meningkatkan akses informasi dalam konteks PAI. Penelitian ini mengkaji bagaimana teknologi AI dapat berkontribusi pada peningkatan kualitas PAI. Perkembangan teknologi yang pesat memberi peluang bagi AI untuk merevolusi metode pembelajaran dan interaksi antara pendidik dan peserta didik. AI, sebagai bidang ilmu yang berfokus pada pengembangan komputer dan sistem yang mampu menjalankan tugas yang memerlukan kecerdasan manusia, berpotensi memberikan manfaat signifikan dalam pendidikan. Dalam konteks pendidikan dasar, kehadiran AI dapat mengoptimalkan proses pembelajaran. Dengan memanfaatkan teknologi AI, guru dapat memantau kemajuan belajar siswa secara individual dan mengidentifikasi kelemahan atau kebutuhan khusus yang perlu diatasi. Sistem AI pun dapat memberikan rekomendasi pembelajaran yang disesuaikan dengan kebutuhan siswa, sehingga meningkatkan efektivitas proses pendidikan.